2015
DOI: 10.1890/150103
|View full text |Cite
|
Sign up to set email alerts
|

Urban climate and adaptation strategies

Abstract: Urban planning scholars Neuman and Smith once wrote that, "Cities and infrastructure have always been mutually interdependent and coevolutionary. In fact, cities could not exist without infrastructure" (Neuman and Smith 2010). Today, urban climate, and specifically extreme heat, pose a threat to both urban residents and ecosystems. These new problems challenge us to redefine what constitutes infrastructure and necessary urban services. To be effective, heat mitigation strategies must coordinate infrastructure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(49 citation statements)
references
References 21 publications
1
46
0
2
Order By: Relevance
“…In support of mitigation plans, satellite imagery in the thermal infrared (TIR) can be used as a tool to identify thermal "hot spots" and "cold spots" and correlate the state of the thermal environment to land use composition [17][18][19][20]. "Hot spots" and "cold spots" are defined as areas which consistently demonstrate higher or lower land surface temperature (LST), respectively, as compared to their surrounding areas.…”
Section: Introductionmentioning
confidence: 99%
“…In support of mitigation plans, satellite imagery in the thermal infrared (TIR) can be used as a tool to identify thermal "hot spots" and "cold spots" and correlate the state of the thermal environment to land use composition [17][18][19][20]. "Hot spots" and "cold spots" are defined as areas which consistently demonstrate higher or lower land surface temperature (LST), respectively, as compared to their surrounding areas.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, heat management strategies fall into three categories: (1) utilizing green infrastructure to lower the ambient temperature [15][16][17][18]; (2) modifying urban form to improve ventilation potential and heat release [19,20]; (3) using advanced technology and materials to cool buildings and the environment [21]. Beyond that, mitigation efforts should consider land-use planning strategies within cities [22], especially in the early stage of the urban planning process.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the artificial infrastructure, the air temperature recorded at 1.0–1.5 m above the substrata was higher than in the natural habitat despite similar wind speeds. It appears, therefore, that rip‐raps effectively maintains higher air temperatures than other neighboring areas, a pattern commonly observed within the urban environment (Larsen, ; Oke, ). In this context, in our study we observed that air temperature decreased at late evening (during sunset) in the natural boulder field, but maintained >1.5°C higher in the artificial habitat.…”
Section: Discussionmentioning
confidence: 78%
“…It appears, therefore, that rip-raps effectively maintains higher air temperatures than other neighboring areas, a pattern commonly observed within the urban environment (Larsen, 2015;Oke, 1988).…”
Section: Could Artificial Infrastructures Modify Coastal Microclimate?mentioning
confidence: 78%
See 1 more Smart Citation